A Comparative Numerical Investigation of the Behavior of Two‐Phase Hydrocarbon Flow Phenomena in Horizontal Flowline with Different Turbulence Models Using OpenFOAM. Issue 2 (30th November 2022) - Sunday, Nsidibe; Settar, Abdelhakim; Chetehouna, Khaled; Gascoin, Nicolas
Abstract: Two‐phase flow in pipes finds application in many industrial activities, mostly in the energy sector, necessitating model systems that correctly predict flow behaviors like flow pattern, pressure drop, and liquid holdup during the design and planning of a fluid transport system. This study aims to analyze three‐dimensional two‐phase liquid‐gas flows in a horizontal flowline. InterFoam, a transient two‐phase solver, was first modified to implement the low‐Reynolds number (LRN) k‐ε model in the OpenFOAM source code. This LRN k‐ε turbulence model is utilized to resolve the turbulence phenomena within the two‐phase mixtures. The two‐phase flow is calculated by using the developed solver based on the volume‐of‐fluid approach. Flow pattern results at different superficial gas and liquid velocities are validated by experimental data from the literature. Then, three Reynolds‐averaged Navier‐Stokes models were used for computations: LRN k‐ε, standard k‐ε, and the shear stress transport k‐ω model. Abstract : Model systems that correctly predict flow patterns and pressure drop are very important during the design and planning of hydrocarbon transport systems. A computational fluid dynamics simulation was carried out on a half‐pipe using OpenFOAM based on the volume‐of‐fluid method.